Questions and answers about recycling and rubbish - Daynes, Katie; Donnelly, Peter (London : Usborne Publishing., Usborne House, 2020)
A fabulous overview of what happens to our waste, from stinking problems and hi tech sorting systems to the importance of make less rubbish in the first place. Includes top tips on how we can reduce and re-use.
Keywords: Recycling; Waste